Work-integrated curriculum transformation and autopedagogical competence in prospective teachers - Tynyskhanova, Aiym; Yessenova, Kalbike; Xoldarova, Irodakhon; Ismailova, Fariza; Zhunusbekova, Aziza (Institute of Advanced Engineering and Science, 2025)
Despite substantial investments in higher education, many Kazakhstani graduates face challenges in securing employment due to a lack of essential job-related competencies. The predominant discipline-based learning approach in Kazakhstani universities often fails to cultivate autopedagogical competence—a critical skill for applying knowledge in real-world contexts and solving practical problems. This study aims to examine the impact of work-integrated curriculum (WIC) transformation on the development of student autopedagogical competence (SAC). A non-experimental quantitative research design was employed, utilizing survey techniques to collect data from a sample of 180 students in Kazakhstan. The sample was determined through random stratified sampling to ensure representativeness. Data analysis was conducted using structural equation modeling (SEM) to identify relationships between dependent (autopedagogical competence), independent (WIC transformation), and moderating variables. The findings reveal that curriculum transformation has a significant and positive impact on the development of autopedagogical competencies. Students exposed to work-integrated learning (WIL) demonstrate stronger self-directed learning capabilities, enhancing their readiness for workforce integration and lifelong professional development. These insights highlight the necessity of innovative curriculum strategies to bridge the gap between academic learning and practical skill acquisition, offering valuable guidance for educators seeking to improve vocational education outcomes.